Indirect fluorescent test for detection of anti-Paracoccidioides brasiliensis antibodies using coated bentonite particles as antigen - Chamma, L. G. [UNESP]; Fábio, W. F. [UNESP]; Bacchi, M. M. [UNESP]; Franco, M. F. [UNESP] (Oxford University Press (OUP), 1983)
An indirect fluorescent test was developed for detecting antibodies to Paracoccidioides brasiliensis using bentonite particles as antigen (Bent-IF). The bentonite particles were coated with P. brasiliensis polysaccharide antigen and tested with sera from paracoccidioidomycosis patients (36 sera), normal blood donors (32 sera) and patients with non-mycotic diseases (29 sera). The titres given by the positive sera were compared with those of complement fixation (CF), immunodiffusion (ID) and immunofluorescent test using yeast forms of the fungus as antigen (conventional-IF). All normal blood donors' sera gave a negative Bent-IF, conventional-IF, ID and CF tests. All paracoccidioidomycosis sera were reactive in conventional-IF and gave concordant results in Bent-IF. There was no correlation between CF and Bent-IF titres. 27·6% of sera from patients with non-mycotic diseases gave weak titres in both IF-tests. The present data indicate that the Bent-IF is a sensitive and simple serodiagnostic technique comparable with the conventional P. brasiliensis antibody test. © 1983.
Keywords: bentonite; fungus antibody; fungus antigen; comparative study; complement fixation test; fluorescent antibody technique; fungus; human; immunodiffusion; immunology; Paracoccidioides; South American blastomycosis; Antibodies, Fungal; Antigens, Fungal; Bentonite; Comparative Study; Complement Fixation Tests; Fluorescent Antibody Technique; Fungi; Human; Immunodiffusion; Paracoccidioidomycosis; Support, Non-U.S. Gov't